REHABILITACJAEffects of cardiac rehabilitation after Bentall procedure - Szykowska-Styczyrz, Joanna; Ferdynus, Grzegorz; Cieślik, Artur (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: The process of vascular “ageing” is connected with the loss of resilience and elasticity of the wall due to a decrease in the quantity of the structural proteins elastin and collagen, as well as degenerative changes in the fibres of the muscular layer, such as cystic necrosis. This leads to a pathological widening of the thoracic aortic wall and in 60% to an ascending aortic aneu-rysm, which may require surgical intervention [1, 2]. Aim: The aim of this work is to evaluate the safety and efficacy of comprehensive early cardiac rehabilitation in a group of 29 high risk patients, with mean age 55 y/o, with a diagnosed ascending aortic aneurysm, treated cardiosurgically by implanting a Da-cron prosthesis with a valve and re-implanting coronary arteries using the Bentall method. Material and methods: The study encompassed 29 patients after Bentall surgery, referred to the Cardiac Rehabilitation Ward of the “Zdrowie” Spa Hospital from January 2008 to January 2009. The patients’ available perioperative data were collated, together with information as to their health status. The safety of rehabilitation was adequately monitored. Within a 21-day period, the rehabilitation was conducted according to the classic programme recommended by the Cardiology Section of the Polish Cardiac Society for ischaemic heart disease (depending on the functional status and level of circulatory efficiency). The programme involved mainly interval training with the ergometer and the treadmill, as well as general exercise. Results: The clinical evaluation of patients who underwent cardiac surgery with the Bentall method showed benefits with regard to improved physical efficiency, higher motivation towards safe individual physical activity and a lesser illness-induced sense of fear and isolation. Conclusions: In our opinion, regardless of age, early, comprehensive cardiac rehabilitation is an effective and safe method of restoring overall fitness and improving circulatory efficiency in patients after Bentall-type cardiac surgery.